Highly Efficient Coherent Optical Memory Based on Electromagnetically Induced Transparency - Hsiao, Ya-Fen; Tsai, Pin-Ju; Chen, Hung-Shiue; Lin, Sheng-Xiang; Hung, Chih-Chiao; Lee, Chih-Hsi; Chen, Yi-Hsin; Chen, Yong-Fan; Yu, Ite A; Chen, Ying-Cheng (Physical review letters, 2018)
Quantum memory is an important component in the long-distance quantum communication based on the quantum repeater protocol. To outperform the direct transmission of photons with quantum repeaters, it is crucial to develop quantum memories with high fidelity, high efficiency and a long storage time. Here, we achieve a storage efficiency of 92.0 (1.5)% for a coherent optical memory based on the electromagnetically induced transparency scheme in optically dense cold atomic media. We also obtain a useful time-bandwidth product of 1200, considering only storage where the retrieval efficiency remains above 50%. Both are the best record to date in all kinds of schemes for the realization of optical memory. Our work significantly advances the pursuit of a high-performance optical memory and should have important applications in quantum information science.